Does the biological treatment or membrane separation reduce the antibiotic resistance genes from swine wastewater through a sequencing-batch membrane bioreactor treatment process. (September 2018) - Sui, Qianwen; Jiang, Chao; Zhang, Junya; Yu, Dawei; Chen, Meixue; Wang, Yawei; Wei, Yuansong
Abstract: Swine wastes are the reservoir of antibiotic resistance genes (ARGs), which can potentially spread from swine farms to the environment. This study establishes a sequencing-batch membrane bioreactor (SMBR) for ARG removal from swine wastewater, and analyzes the effect of biological treatment and membrane separation on the ARG removal at different solid retention times (SRTs). The SMBR removed 2.91 logs (copy number) of ARGs at a short SRT (12 days). Raising the SRT reduced the removal rates of the detected genes by the biological treatment. Under the relative long SRT (30 days), ARGs and mobile genetic elements (MGEs) were maximized within the reactor and were well removed by membrane separation, with the average genes removal rate of 2.95 (copy number) and 1.18 logs (abundance). At the relatively low SRT, the biological treatment showed the dominant ARG removal effect, while the membrane separation took the advantages of ARG removal especially at the relatively long SRT. The ARG profile was related to the shift of the microbial community structure. The ARGs coexisted with the functional bacteria (ammonia oxidizing bacteria, nitrite oxidizing bacteria and denitrifiers), suggesting they are hosted by the functional bacteria. Graphical abstract: Highlights: SMBR reduced the ARGs (copy number) by 2.91 logs at SRT of 12 days. Raising the SRT reduced the removal of ARGs by the biological treatment. Membrane separation reduced ARGs by 1.83 logs, no obvious dependence on SRT. Co-occurrence of functional bacteria (AOB, NOB and denitrifiers) with ARGs